Reusable cobalt catalyst for reversible acceptorless dehydrogenation and hydrogenation of N-Heterocycles - Jaiswal, Garima; Subaramanian, Murugan; Sahoo, Manoj K.; Balaraman, Ekambaram (ChemCatChem, 2019)
<span style="color: rgb(42, 45, 53); font-family: "Source Sans Pro", Arial, Helvetica, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(248, 248, 248);">The development of robust catalytic systems based on basemetals for reversible acceptorless dehydrogenation (ADH) and hydrogenation of feedstock chemicals is very important in the context of ` hydrogen storage'. Herein, we report a highly efficient reusable cobalt-based heterogeneous catalyst for reversible dehydrogenation and hydrogenation of N-heterocycles. Both the ADH and the hydrogenation processes operate under mild, benign conditions.